2021
DOI: 10.1038/s41598-021-91971-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changing guidelines on genetic testing and surveillance recommendations in a contemporary cohort of breast cancer survivors with family history of pancreatic cancer

Abstract: Changing practice guidelines and recommendations have important implications for cancer survivors. This study investigated genetic testing patterns and outcomes and reported family history of pancreatic cancer (FHPC) in a large registry population of breast cancer (BC) patients. Variables including clinical and demographic characteristics, FHPC in a first or second-degree relative, and genetic testing outcomes were analyzed for BC patients diagnosed between 2010 and 2018 in the NYU Langone Health Breast Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The size of the genetic panels used for cancer patients’ evaluation has progressively increased in recent years [ 50 ]. Consequently, the findings derived from these expanded panels are still in the preliminary stages, and it is impossible to directly compare the new data with previous results from shorter panels.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the genetic panels used for cancer patients’ evaluation has progressively increased in recent years [ 50 ]. Consequently, the findings derived from these expanded panels are still in the preliminary stages, and it is impossible to directly compare the new data with previous results from shorter panels.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diagnostics is also widely used in oncology, as it allows diagnosis of hereditary cancer syndromes (e.g., breast and/or ovarian cancer), precise diagnosis of the tumor (molecular classification of tumors, e.g., brain gliomas), determining the patient’s susceptibility to targeted treatment (use of optimally acting drugs in patients with a specific mutation in cancer cells; predictive tests), and establishing the prognosis of the disease (prognostic tests) (Kilbride and Bradbury 2020 ; Wang et al 2021 ; Mandrell et al 2021 ).…”
Section: Genetic Counseling and Tests For Medical Purposesmentioning
confidence: 99%
“…4 Additionally, variation in testing criteria guidelines, especially as these change over time, and guidelines failing to capture all affected patients exacerbate difficulties for health care providers to identify patients to refer for adequate care. [5][6][7][8][9][10][11] Unfortunately, historically underserved populations tend to fare worse. Several studies have shown that racial and ethnic minorities are less likely to receive referrals, undergo genetic counseling, and ultimately receive genetic testing.…”
Section: Introductionmentioning
confidence: 99%